2018
DOI: 10.3344/kjp.2018.31.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Pain medication and long QT syndrome

Abstract: Long QT syndrome is a cardiac repolarization disorder and is associated with an increased risk of torsades de pointes. The acquired form is most often attributable to administration of specific medications and/or electrolyte imbalance. This review provides insights into the risk for QT prolongation associated with drugs frequently used in the treatment of chronic pain. In the field of pain medicine all the major drug classes (i.e. NSAIDs, opioids, anticonvulsive and antidepressant drugs, cannabinoids, muscle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Drug-induced QT interval prolongation is a critical issue [18]. Drugs leading to fatal heart rhythm disorders should be prescribed with caution because life-saving drugs can also lead to life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-induced QT interval prolongation is a critical issue [18]. Drugs leading to fatal heart rhythm disorders should be prescribed with caution because life-saving drugs can also lead to life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors implicated in acquired LQTS are female sex, age > 65 years and occult genetic predisposition for LQTS [18]. Risk factor that can be modulated to prevent QT interval prolongation is electrolyte imbalance including hypokalemia, hypomagnesemia, and hypocalcemia.…”
Section: Contributing Factorsmentioning
confidence: 99%
“… 23 Pharmacodynamic drug interactions between medications commonly prescribed for pain and related comorbidities may increase risk of respiratory sedation and death (eg, benzodiazepines, gabapentinoids, opioids), 24 , 25 serotonin syndrome (eg, antidepressants, certain opioids, triptans), 26 excessive anticholinergic effects (eg, tricyclic antidepressants, opioids, muscle relaxants) 27 or QT interval prolongation (eg, methadone, antidepressants, NSAIDs, muscle relaxants). 28 Patients may be seeing both primary care teams and specialists to manage their physical and mental health conditions, with the pharmacist and the pharmacy as the common convergence point. As such, pharmacists are essential in assessing the medication regimen in its totality.…”
Section: Role In Medication Managementmentioning
confidence: 99%
“…Prucalopride is a serotonin receptor agonist with a selective high-affinity for intestinal 5-hydroxy tryptamine 4 (5-HT4) receptors, which have prokinetic effects, promoting peristalsis and defecation. At therapeutic doses, it does not inhibit human ether-a-go-go-related gene (hERG) potassium channels, (which are known to play a pivotal role in long-QT syndrome) and has no proarrhythmic effect, unlike the structurally related cisapride (which has been withdrawn from the market) [55,56]. While one placebo-controlled study failed to show a statistically significant increase in spontaneous bowel movements, even as 52% of participants reported adverse reactions [57], another trial reported significant improvement of OIC with prucalopride [58].…”
Section: Main Bodymentioning
confidence: 99%